2013
DOI: 10.1111/febs.12518
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ca2+ in folding the tandem β‐sandwich extender domains of a bacterial ice‐binding adhesin

Abstract: -bound immunoglobulin-like b-sandwich. Ca 2+ ions are coordinated at the interfaces between each RII monomer and its symmetry-related molecules, suggesting that these ions may be involved in the stabilization of the tandemly repeated RII. We hypothesize that > 600 Ca 2+ ions help to rigidify the chain of 104-residue repeats in order to project the ice-binding domain of MpAFP away from the bacterial cell surface. The proposed role of RII is to help the strictly aerobic bacterium bind surface ice in an Antarctic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…We have previously shown that the RII-tandemer is fully structured in 10 molar equivalents of Ca 2+ but resembles a random coil in the absence of this ion [12]. Similar analyses were applied to the RII tetra-tandemer.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…We have previously shown that the RII-tandemer is fully structured in 10 molar equivalents of Ca 2+ but resembles a random coil in the absence of this ion [12]. Similar analyses were applied to the RII tetra-tandemer.…”
Section: Resultsmentioning
confidence: 91%
“…The lipopolysaccharide layer also confers to the bacterial outer membrane an overall negative charge. Mp AFP_RII is rich in negatively charged acidic residues (18% Asp+Glu), and contains no Lys or Arg [12]. The acidic residues of RII not only help coordinate Ca 2+ to stabilize the protein's fold, but also may be repelled from the negatively charged cell surface for better extension of the ice-binding domain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations